Microstructural Characterizations and Radiation Shielding Quantities of Rice Husk Ash-Based Self-Compacting Concrete and Its Precursors - Plando, Floyd Rey P. (Archīum Ateneo, 2023)
This paper investigates the microstructural, chemical, and radiation shielding characteristics of rice husk ash-based self-compacting concrete (RHA-SCC) and its precursors – rice husk ash (RHA) and ordinary Portland cement (OPC). Several radiation attenuation parameters of RHA-SCC, RHA, and OPC have been studied using EpiXS. Characterizations of these samples using FTIR, XRD, and SEM were also employed for chemical bonds, mineral phase, and morphological analysis, respectively. The XCOM data library was utilized to obtain mass attenuation coefficients (MAC) and related to EPICS2017 and EPDL97 data. From the results, prominent interaction mechanisms for RHA-SCC were photoelectric absorption, incoherent scattering, and pair production in the nuclear field. Both the mean free path (MFP) and half-value layer (HVL) values agreed to this sequence: OPC > RHA > RHA-SCC. The Zeff values recorded for high-photon energies were 13.95, 13.20, and 10.85 for RHA-SCC, RHA, and OPC, respectively. While maximum Neff was estimated at the low-energy region with values of 4.68, 4.70, and 3.89 electrons·g−1 for RHA-SCC, RHA, and OPC. Both buildup factors were highly affected by the presence of higher Z elements contained in RHA-SCC, reaching up to 200 keV at 40 MFP. For intermediate and higher-energy levels, the MAC values established this order: RHA-SCC > OPC > RHA, with the lowest deviation of 0–0.21% for EPICS2017-EPDL97 tandem. Overall, RHA-SCC has better shielding effects compared to its precursors and can cost-effectively be used as an additive in preparing radiation shielding concrete.